Functional Results after Repair of Large Hiatal Hernia by Use of a Biologic Mesh - Antonakis, Filimon; Köckerling, Ferdinand; Kallinowski, Friedrich (Frontiers in Surgery, 2016)
Background: The aim of this observational study is to analyze the results of patients with large hiatal hernia and upside-down stomach after surgical closure with a biologic mesh (Permacol®, Covidien, Neustadt an der Donau, Germany). Biologic mesh is used to prevent long-term detrimental effects of artificial meshes and to reduce recurrence rates. Methods: A total of 13 patients with a large hiatal hernia and endothoracic stomach, who underwent surgery between 2010 and 2014, were included. Interviews and upper endoscopy were conducted to determine recurrence, lifestyle restrictions and current complaints. Results: After a mean follow-up of 26+18 months (range 3-58) months 10 patients (three men, mean age 73+13, range 26-81 years) were evaluated. A small recurrent axial hernia was found in one patient postoperatively. Dysphagia was the most common complaint (four cases), while in one case the problem was solved after endoscopic dilatation. In three cases bloat and postprandial pain were documented. In one case explantation of the mesh was necessary due to mesh migration and painful adhesions. In one further case with gastroparesis pyloroplasty was performed without success. Conclusion: Recurrence was rare after hernia repair with the biologic mesh Permacol®. Dysphagia, gas bloat and intraabdominal pain were frequent complaints. Despite the small number of patients it can be concluded that a biologic mesh may be an alternative to synthetic meshes to reduce recurrences. Long-term results should be studied in the future in order to assess the potential of biologic meshes to preserve esophageal function as well. This is important since artificial meshes are known to erode the esophagus after 5–10 years.